Effect of Edible Coatings on the Quality of Cactus Stems (Opuntia sp) During Cold Storage - Villegas-Ochoa, Mónica A.; Rodríguez-Félix, Armida; Fortiz-Hernández, Judith (Journal of the Professional Association for Cactus Development, 2020)
The quality of tender cactus stems (Opuntia ficus-indica) during cold storage is affected by weight loss and chilling injury. These disorders have been reduced in several fruits and vegetables by covering the product with edible coatings. The effect of application of two edible coatings (Semperfresh® and another formulation based on carboxymethylcellulose, CMC, named Wax 1) on the quality of tender cactus stems of two cultivars (COPENA F-1 and COPENA V-1) stored for 30 days at 5 and 10°C was evaluated. Weight loss, color (hue angle, chroma and L* value), permeability of cuticles to water vapor, chilling injury (CI), and rot, were recorded periodically. Cladodes of COPENA V-1 were more susceptible to CI and rots during storage at 5 y 10°C than cladodes of COPENA F-1. Wax treatment effect on quality of cactus stems during storage was different on evaluated cultivars and storage temperature. The beneficial effect of Semperfresh wax use were a reduction in weight loss, color changes (hue), CI and rots during storage at 5°C of cactus stems of COPENA V-1, as well as a reduction in weight loss of cladodes of both cultivars stored at 10°C. Wax 1 reduced CI at 5°C and rots at 10°C of cladodes of COPENA V-1. However, Wax 1 increased CI of cladodes of COPENA F-1 and weight loss of cladodes of COPENA F-1 and COPENA V-1 stored at 10°C.